Sistema de gestão ambiental: estudo de caso da Mineradora de Ouro Rio Paracatu Mineração - RPM - BOWEN, Dilma Assis Silveira (2019)
A Preliminary Assessment of the Environmental Management System employed by the company Rio Paracatu Mineração – RPM that performs extraction of gold in the namesake city in the north of Minas Gerais, showed that the anthropic impacts on physical, biotic and chemical means are controlled in a satisfactory manner. The methodology used for preparing the diagnostic system was proposed by the author with the conceptual basis to ISO 14000 and Faria in 2006. This model allows the viewing of the performance management of company's SGA. The indicators discussed here are important to demonstrate wich items the high direction of the RPM must intensify its actions in pursuit of continuous improvement. The comparison of sections examined is shown in graph, so the organization can be developed with sustainability is essential that these basic elements are in balance, requiring, therefore, a commitment to continuous improvement among all employees of the institution and the results must reach a performance of 75 to be considered sustainable.